Encapsulation and solid state sequestration of gases by calix[6]arene-based molecular containers. Issue 48 (1st June 2017) - Lavendomme, Roy; Ajami, Daniela; Moerkerke, Steven; Wouters, Johan; Rissanen, Kari; Luhmer, Michel; Jabin, Ivan
Abstract : Calix[6]arene-based molecular containers can encapsulate small guests through a unique "rotating door" complexation process. The sequestration in the solid state of greenhouse gases is demonstrated. Abstract : Two calix[6]arene-based molecular containers were synthesized in high yields. These containers can encapsulate small guests through a unique "rotating door" complexation process. The sequestration of greenhouse gases is clearly demonstrated. They can be stored in the solid state for long periods and released via dissolution of the inclusion complex.